2012
DOI: 10.1186/1423-0127-19-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic variant on chromosome 12p13 and stroke survival and recurrence: a one year prospective study in Taiwan

Abstract: BackgroundThe association between ischemic stroke and 2 single nucleotide polymorphisms (SNPs) on chromosome 12p13, rs12425791 and rs11833579 appears inconsistent across different samples. These SNPs are close to the ninjurin2 gene which may alter the risk of stroke by affecting brain response to ischemic injury. The purpose of this study was to investigate the association between these two SNPs and ischemic stroke risk, as well as prognostic outcomes in a Taiwanese sample.MethodsWe examined the relations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 16 publications
2
57
1
1
Order By: Relevance
“…Our results are in agreement with three other studies [6,[13][14][15] carried out in Chinese populations, but inconsistent with three other studies [10][11][12]. The result of our study in the Guangxi Han population was inconsistent with a previous genome-wide association study in Caucasians [5].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our results are in agreement with three other studies [6,[13][14][15] carried out in Chinese populations, but inconsistent with three other studies [10][11][12]. The result of our study in the Guangxi Han population was inconsistent with a previous genome-wide association study in Caucasians [5].…”
Section: Discussionsupporting
confidence: 52%
“…In contrast, a significant association between rs12425791 and IS was found in a large populationbased case-control study in Japan [9]. Three studies [10][11][12] reported that rs12425791 was associated with IS risk in Chinese populations, whereas no evidence of association between rs12425791 and IS was found in three other studies [6,[13][14][15]. It seems that the association between rs12425791 and IS differs among different ethnic populations, including Chinese populations.…”
Section: Introductionmentioning
confidence: 64%
“…Autophagy plays a pivotal role not only in normal liver physiology, but also in the pathogenesis of many liver diseases including nonalcoholic and alcoholic fatty liver and viral hepatitis (Mao et al 2016; Tang et al 2012). Acute T. cruzi infection may adapt lipophagic pathway to survive energy starvation by increasing autophagic sequestration of lipid droplets and their degradation in hepatic lysosomes.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of genome-wide association studies from prospective cohorts identified a locus on 12p13 near the NINJ2 gene associated with incident ischemic stroke, 71 but large case-control studies have not replicated this finding. 72,73 This inconsistency may be because of a possible effect of this locus on stroke mortality, 74 a synthetic association from rare variants not well represented in the subsequent replication studies, or a false-positive association. Recent meta-analyses of large case-control studies have identified novel genetic associations with specific stroke subtypes, suggesting that risk factor profiles and pathological mechanisms may differ across subtypes.…”
Section: Generally Nonmodifiable Risk Factors and Risk Assessmentmentioning
confidence: 99%